Quality Control (IntechOpen, 2023)
Quality control has played an important role in the manufacture of goods and the creation of monuments since antiquity. From the development of Heron’s first robot and the Antikythera mechanism to today’s Internet of Things (IoT), Industry 4.0, and artificial intelligence, quality control has undeniably come a long way. This book examines quality control in several different scenarios and locations. Chapters discuss quality control of Nigeria’s road network, Ethiopia’s leather industry, Africa’s food industry, and Hong Kong’s construction sector, among other scenarios. The book also discusses quality control of intrusion detection systems, artificial intelligence, complementary metal oxide semiconductors, and more.